Promotion, Relative Performance Information, and the Peter Principle - Chan, Eric W. (The Accounting Review, 2018)
ABSTRACT I examine the effects of providing workers with relative performance information (RPI) on employers' promotion decisions and the impact of those decisions on worker performance. In my experimental setting, the job after promotion requires higher-level abilities than the current job. I find that workers increase their effort to improve their current job performance after a promotion opportunity is announced because they expect this to increase their chances of promotion, even though the new task requires higher-level abilities. Moreover, because employers anticipate that workers who have RPI will react negatively if they see that the best current job performer is not promoted, employers promote the best current job performer, rather than the worker best suited for the next job, more often when workers have RPI than when they do not. Consistent with the Peter Principle, I find that when workers have RPI, the promoted worker's performance is lower after promotion because the promoted worker lacks the ability to perform the new job well. Finally, in a supplemental experiment, I find that providing workers with feedback on their abilities to perform the next job, in addition to current job RPI, improves the effective sorting of workers, but it comes at the cost of reduced promotion-based incentives. My results suggest that, notwithstanding the benefits documented in previous studies, RPI also imposes potential costs that firms should take into account when deciding whether to provide workers with RPI. JEL Classifications: M41; M51; M52. Data Availability: Contact the author.